Honey potentially mitigates morphine analgesic tolerance and physical dependence in rats (Bangladesh Journal of Medical Science, 2018)
Introduction:Honey has been used traditionally in medicine as well as food supplements. Honeybees are said to be able to cure many diseases. However, its influences on opioid tolerance and dependence have not yet been clarified.Materials and Methods:Adult male Sprague- Dawley rats were rendered tolerant to the analgesic effect of morphine by injection of morphine (10 mg/kg, i.p.) twice daily for 14 days. To develop morphine dependence rats given escalating doses of chronic morphine. To determine the effect of stingless bee honey on the development of morphine tolerance and dependence. The hotplate and naloxone precipitation tests were used to assess the degree of tolerance and dependence, respectively.The results: Our results showed that chronic morphine-injected rats displayed tolerance to the analgesic effect of morphine as well as morphine dependence. Methadone+morphine (MetM), methadone+morphine+ honey (MetMH) and morphine+Honey (MH) significantlylower the development of morphine tolerance with p-value p